Support material drainage system design for 3D printed foams - Ho, Zhao Yi (2016)
3D printing is an emerging technology that is useful in many applications such as healthcare and aerospace industry. The customizability and ability to print different materials simultaneously are several benefits of 3D printing over conventional methods. In the context of producing foams through 3D printing using ProJet 5500X, a drawback would be the efficiency and possibility of removing the wax support material. The aim is to reduce post-processing time of the parts for it to be less likely to affect the material properties. This requires more in depth investigation of flow through porous structures. By applying Darcy’s law, it is evident that the flow is mainly dependent on the permeability of the structure. Factors that affect the permeability of the structures are studied by having several structures with different pore sizes and shapes being tested in ANSYS. Preliminary results pointed out several factors that affect the permeability which could be useful prior to designing the product using computer-aided software.